r_{1} = outer radius

r_{2} = inner radius

C_{1} = outer circumference

C_{2} = inner circumference

A_{1} = area of circle of r_{1}

A_{2} = area of circle of r_{2}

A_{0} = shaded area

The online annuluses calculator to find the area, circumference and radius of an annulus. When you know two known variable, then select from the droplist, calculate the other 5 unknowns.

### Annulus Formulas:

**Given r**_{1} and r_{2}:

C_{1} = 2πr_{1}

C_{2} = 2πr_{2}

A_{1} = πr_{1}^{2}

A_{2} = πr_{2}^{2}

A_{0} = A_{1} - A_{2}.

**Given r**_{1} and C_{2}:

r_{2} = C_{2} / 2π

C_{1} = 2πr_{1}

A_{1} = πr_{1}^{2}

A_{2} = πr_{2}^{2}

A_{0} = A_{1} - A_{2}.

**Given r**_{1} and A_{2}:

r_{2} = √(A_{2} / π)

C_{1} = 2πr_{1}

C_{1} = 2πr_{2}

A_{1} = πr_{1}^{2}

A_{0} = A_{1} - A_{2}.

**Given r**_{2} and C_{1}:

r_{1} = C_{1} / 2π

C_{2} = 2πr_{2}

A_{1} = πr_{1}^{2}

A_{2} = πr_{2}^{2}

A_{0} = A_{1} - A_{2}.

Given C_{1} and C_{2}:

r_{1} = C_{1} / 2π

r_{2} = C_{1} / 2π

A_{1} = πr_{1}^{2}

A_{2} = πr_{2}^{2}

A_{0} = A_{1} - A_{2}.

**Given C**_{1} and A_{2}:

r_{1} = C_{1} / 2π

r_{2} = √(A_{2} / π)

C_{2} = 2πr_{2}

A_{1} = πr_{1}^{2}

A_{0} = A_{1} - A_{2}.

**Given r**_{2} and A_{1}:

r_{1} = √(A_{1} / π)

C_{1} = 2πr_{1}

C_{2} = 2πr_{2}

A_{2} = πr_{2}^{2}

A_{0} = A_{1} - A_{2}.

**Given C**_{2} and A_{1}:

r_{1} = √(A_{1} / π)

r_{2} = C_{2} / 2π

C_{1} = 2πr_{1}

A_{2} = πr_{2}^{2}

A_{0} = A_{1} - A_{2}.

**Given A**_{1} and A_{2}:

r_{1} = √(A_{1} / π)

r_{2} = √(A_{2} / π)

C_{1} = 2πr_{1}

C_{2} = 2πr_{2}

A_{0} = A_{1} - A_{2}.

**Given r**_{1} and A_{0}:

C_{1} = 2πr_{1}

A_{1} = πr_{1}^{2}

A_{2} = A_{1} - A_{0}

r_{2} = √(A_{2} / π)

C_{2} = 2πr_{2}.

**Given r**_{2} and A_{0}:

C_{2} = 2πr_{2}

A_{2} = πr_{2}^{2}

A_{1} = A_{0} + A_{2}

r_{1} = √(A_{1} / π)

C_{1} = 2πr_{2}.

**Given C**_{1} and A_{0}:

r_{1} = C_{1} / 2π

A_{1} = πr_{1}^{2}

A_{2} = A_{1} - A_{0}

r_{2} = √(A_{2} / π)

C_{2} = 2πr_{2}.

**Given C**_{2} and A_{0}:

r_{2} = C_{2} / 2π

A_{2} = πr_{2}^{2}

A_{1} = A_{0} + A_{2}

r_{1} = √(A_{1} / π)

C_{1} = 2πr_{1}.

**Given A**_{1} and A_{0}:

A_{2} = A_{1} - A_{0}

r_{1} = √(A_{1} / π)

r_{2} = √(A_{2} / π)

C_{1} = 2πr_{1}

C_{2} = 2πr_{2}.

**Given A**_{2} and A_{0}:

A_{1} = A_{0} + A_{2}

r_{1} = √(A_{1} / π)

r_{2} = √(A_{2} / π)

C_{1} = 2πr_{1}

C_{2} = 2πr_{2}.